A guide to publishing for academics inside the publish or perish phenomenon - Liebowitz, Jay 1957- (CRC Press, 2015)
A Guide to Publishing for Academics provides useful knowledge from leading journal editors of both traditional and online journals, as well as various tiers of journals. Although the focus is mainly in the business and IT areas, much of the guidance provided can cross into other fields. The book contains interesting vignettes and do's and don'ts so that potential authors can understand what goes on behind the scenes once the manuscript arrives on the journal editor's desk